Robust cooperative control of multi-agent systems : a prediction and observation prospective /: a prediction and observation prospective. (2021) - Wang, Chunyan, 1983-; Zuo, Zongyu, 1982-; Wang, Jianan, 1982-; Ding, Zhengtao
No abstract available